Research on the Design, Preparation and Application of Core-Shell Nanocapsules - Li, Yifan (Transactions on Environment, Energy and Earth Sciences, 2026)
A 160 nm monodisperse core shell nanocapsule architecture integrates three hierarchical diffusion control strata: core Stokes Einstein viscosity damping, shell polymer free volume obstruction, and outer layer electro steric shielding. These are embedded within a single step low shear solvent displacement interfacial polycondensation protocol that eliminates secondary emulsification. Continuum scale modeling quantitatively links core viscosity, shell cross link density and surface zeta potential to predict the effective diffusion coefficient and the magnitude of stimulus triggered permeability jumps. Experimental validation yields carriers that reproducibly exhibit below 10 percent initial burst release, below 50 ppm residual solvent, above 80 percent biphasic loading efficiency, and simultaneous compliance with food grade oral safety intestinal targeting and textile grade laundering durability air permeability metrics. The unified framework furnishes a mechanistic regulation aligned sector agnostic design toolkit for next generation programmable nano delivery systems, bridging molecular level diffusion physics with scalable green manufacturing and cross industry performance benchmarks while offering immediate translational utility for functional foods, nutraceuticals, cosmeceuticals and smart textiles.
Keywords: Core-shell nanocapsule; continuum diffusion model; burst suppression; low-shear nanomanufacturing; programmable release.